An Improved Method Development and Validation for the Quantification of Clomifene in Pharmaceutical Formulation and Biological Matrix by LC-MS/MS - Kauser, Rubina; Chaitanya, Padavala Sunil Kumar; Venkatesan, Palanivel (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim: The major objective of current work was to create sensitive tandem mass spectrometric method using electrospray ionization and liquid chromatography for quantifying Clomifene in biological matrices Materials and Methods: A stationary Phenomenex C18 column with dimensions of 50 mm×4.6 mm and 5 μ sizes of particles were used to achieve chromatographic elution. Isocratic eluting of components was done using methanol and 0.10% V/V HCOOH in the fraction of 85:15V/V as a movable phasic system. For drug and internal standard separation, liquid-liquid extraction was carried out using methanol and ethyl acetate (1:4) solvent solution. Results: On multiple reaction monitoring, ions of molecular and products were seen at m/z 406.19→125.01 for Clomifene and 450.12→160.03 for Bictegravir internal standard. The drug’s linearity graph had an r2 value of 0.9998 and was rectilinear at concentrations between 400 and 16000 ng/mL. The inter and intra-batch accuracy % relative standard deviation values ranged from 2.54 to 5.21. The percent recovery results of the LQC, MQC and HQC samples were 102.85%, 97.84% and 94.27%, respectively. This approach has made excellent recoveries. Conclusion: Clomifene is more stable for a longer period of time and the developed approach was successfully applicable to routine examination of Clomifene in biological samples.
Keywords: Clomifene; LC-MS/MS; USFDA guidelines; Validation; Stability; Linearity; Matrix effect